Comparative Analysis of Semi Basement Wall With Different Cohesion and Basement Depth in West Jakarta - Luthfy Alfarizi; Resi Aseanto (Journal of World Conference (JWC), 2021)
DKI Jakarta has a population density of 19,516 people / square km. Government of Jakarta in the PERDA DKI Jakarta No. 7-2010 CHAPTER 5 Article 42 Paragraph 1 states that "every building must provide parking space". To overcome this, semi-basement will be an option to make a parking space that does not require too much excavation costs. This analysis will compare two types of retaining walls, cantilever retaining walls and conventional retaining walls using the Rankine method for static conditions and the Mononobe-Okabe method for dynamic conditions. This analysis results in the conclusion that for a depth of 2.00m, conventional walls are found to be more efficient in terms of costs with a difference of up to Rp. 178,700 / m’. For soil with a depth of 1.75m, cost efficiency depends on soil cohesion. For the higher soil cohesion, the cost of making cantilever walls is more efficient, reaching Rp. 130,600 / m '. For soil with a depth of 1.50m, with higher cohesion, the cantilevered wall will be more cost-efficient than conventional wall making, reaching Rp. 232,400 / m’.